Surgical treatment of ductal biliary recurrence of poorly cohesive gastric cancer mimicking primary biliary tract cancer: a case report. Issue 4 (11th April 2022) - Poletto, Edoardo; Ruzzenente, Andrea; Turri, Giulia; Conci, Simone; Ammendola, Serena; Luchini, Claudio; Scarpa, Aldo; Guglielmi, Alfredo
Abstract: Ductal biliary recurrence of cancers arising in other anatomical districts is a rare event, usually observed in the setting of disseminated disease; hence surgery is rarely a viable option. We present the case of a 56-year-old male who underwent subtotal gastric resection 7 years earlier for a poorly cohesive gastric cancer, presenting with obstructive jaundice. Magnetic resonance imaging and computed tomography scan suggested primary malignant obstruction of the main bile duct. Percutaneous transhepatic biliary drainage was performed to palliate jaundice and obtain biopsies; pathological examination suggested a ductal biliary recurrence of gastric carcinoma. Pancreaticoduodenectomy and bile duct resection were performed. Histology, immunohistochemistry and molecular profiling confirmed that the stenosis represented a gastric cancer metastasis. This is the first case of an isolated ductal biliary recurrence of gastric cancer amenable to surgical resection. This clinical case suggests that biliary obstructions in patients with previous oncological history require biliary biopsies to exclude a recurrent disease.